Distorted leukocyte migration, angiogenesis, wound repair and metastasis in Tspan8 and Tspan8/CD151 double knockout mice indicate complementary activities of Tspan8 and CD51 - Zhao, Kun; Erb, Ulrike; Hackert, Thilo; Zöller, Margot; Yue, Shijing (Biochimica et biophysica acta. Molecular cell research, 2018)
The tetraspanin Tspan8 supports via associated integrins and proteases tumor progression and angiogenesis. To shed light on its activities in non-transformed cells, we generated a Tspan8 knockout (ko) mouse, comparing leukocyte migration, angiogenesis, wound healing and tumor growth with wild type, CD151ko and Tspan8/CD151ko (dbko) mice. CD151ko mice were included as CD151 activities resemble that of Tspan8, and dbko mice to exclude mutual substitution. Tspan8ko and dbko mice show no pathological phenotype. However, delayed type hypersensitivity reactions are mitigated in Tspan8ko mice, angiogenesis is severely impaired in Tspan8ko, CD151ko and dbko mice, with Tspan8 mostly affecting lymphangiogenesis. Distinct contributions of CD151 and Tspan8 to skin wound healing rely on preferentially CD151 anchoring basal keratinocytes and Tspan8 promoting motility. Proliferation of wounded skin keratinocytes is not affected. Metastasis formation of a melanoma and a Tspan8-expressing pancreatic cancer line was impaired in Tspan8ko and dbko mice, pointing towards a contribution of host Tspan8 to tumor progression. In line with the importance of tetraspanins in exosome-mediated intercellular communication, defects became mitigated by Tspan8/CD151-competent serum exosomes, which offers a most promising therapeutic option for chronic wounds and arteriosclerosis.
Available online 11 November 2017
Gesehen am 03.04.2020